Studi Literatur Sistem Pengendalian Manajemen di Perusahaan Audit - Adanan Silaban; Manatap Berliana Lumban Gaol (ITB AAS INDONESIA, 2023)
This article aims to examine the relationship between types of management control that can be used together to form a dynamic system to maintain a balance of professional-commercial objectives in audit firms. To achieve this goal, it is carried out by reviewing the literature on the influence of different management controls on auditor behavior and decision making, and adopting the framework of Merchant and Van der Stede (2017); because it allows a clear and unambiguous classification of the different control elements. In the context of the exploratory-exploitation tension, the management control literature on ambidexterity provides a theoretical basis for examining this tension in the context of auditing and it is hoped that results and value-based management control elements play an important role in managing the learning and innovation process in audit firms, where the main responsibility is to actively promoting the learning and innovation process rests with the senior auditors.